Pengaruh Brand Image terhadap Brand Trsut Serta Implikasinya terhadap Brand Loyality (Produk Dodol PT. Herlinah Cipta Pratama) - Wati Susilawati; Wufron Wufron (Jurnal Wacana Ekonomi, 2018)
This research was conducted to determine the effect of brand image on brand trust and its implications for brand loyalty. This study uses a sample of the number of customers at PT Herlinah Cipta Pratama by using a purposive sampling technique. The data used in this study are primary data obtained through distributing questionnaires to company customers with predetermined criteria. The data analysis technique used is regression analysis with mediating variables. The results showed that brand image has a positive and significant effect on brand trust, brand image has a positive and significant effect on brand loyalty, brand trust has a positive and significant effect on brand loyalty, and it is concluded that brand image can have a significant effect on brand loyalty through brand trust.